Exploring the Theoretical Landscape: Implications of Remote Work on Employee Performance and Well-being - Paudel, Ram; Sherm, Alex (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
The COVID-19 pandemic has reshaped the global workforce, propelling remote work from a niche practice to a ubiquitous reality for many organizations. This shift has underscored the need to understand its implications on employee performance and well-being. This research investigates the impact of remote work on employee performance indicators like productivity and task completion rates, as well as its influence on well-being factors such as work-life balance and job satisfaction. Through a synthesis of literature, theoretical frameworks, and empirical data, the study provides insights into the multifaceted dynamics of remote work. Theoretical lenses such as self-determination theory and social identity theory offer valuable perspectives on employee motivations and group dynamics in remote work settings. The research culminates in practical recommendations for organizations, advocating for flexible policies, investment in remote work infrastructure, and support for employee well-being. By bridging theory and practice, this study equips organizations with evidence-based insights to navigate the evolving landscape of remote work and cultivate environments conducive to individual and organizational success in the post-pandemic era.